The Extended N-Terminal Domain Confers Atypical Chemokine Receptor Properties to CXCR3-B - D’Uonnolo, Giulia; Reynders, Nathan; Meyrath, Max; Abboud, Dayana; Uchański, Tomasz; Laeremans, Toon; Volkman, Brian F.; Janji, Bassam; Hanson, Julien; Szpakowska, Martyna; Chevigné, Andy (Frontiers in Immunology, 2022)
The chemokine receptor CXCR3 plays a critical role in immune cell recruitment and activation. CXCR3 exists as two main isoforms, CXCR3-A and CXCR3-B, resulting from alternative splicing. Although the two isoforms differ only by the presence of an N-terminal extension in CXCR3-B, they have been attributed divergent functional effects on cell migration and proliferation. CXCR3-B is the more enigmatic isoform and the mechanisms underlying its function and signaling remain elusive. We therefore undertook an in-depth cellular and molecular comparative study of CXCR3-A and CXCR3-B, investigating their activation at different levels of the signaling cascades, including G protein coupling, β-arrestin recruitment and modulation of secondary messengers as well as their downstream gene response elements. We also compared the subcellular localization of the two isoforms and their trafficking under resting and stimulated conditions along with their ability to internalize CXCR3-related chemokines. Here, we show that the N-terminal extension of CXCR3-B drastically affects receptor features, modifying its cellular localization and preventing G protein coupling, while preserving β-arrestin recruitment and chemokine uptake capacities. Moreover, we demonstrate that gradual truncation of the N terminus leads to progressive recovery of surface expression and G protein coupling. Our study clarifies the molecular basis underlying the divergent effects of CXCR3 isoforms, and emphasizes the β-arrestin-bias and the atypical nature of CXCR3-B.